Studi Deskriptif pada Sikap Ayah dan Ibu dalam Upaya Pencegahan Stunting - Dimas Aqila; Nopi Nur Khasanah; Kurnia Wijayanti (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Background: Stunting remains a chronic nutritional problem with long-term impacts on children’s growth and development. Stunting prevention efforts are not solely dependent on health interventions but are also strongly influenced by parental attitudes, particularly those of fathers and mothers, regarding nutrition fulfillment, parenting practices, and family health behaviors. Objective: This study aimed to describe the attitudes of fathers and mothers toward stunting prevention efforts. Method: his study employed a descriptive quantitative design. Data were collected using a structured questionnaire administered to parents of children under five years old, with sampling conducted according to the study criteria. Descriptive analysis was used to illustrate respondents’ characteristics and parental attitudes toward stunting prevention. Results: The results indicated that most fathers and mothers demonstrated positive attitudes toward stunting prevention, particularly in nutritional fulfillment and utilization of health services. However, suboptimal attitudes were still identified in several aspects, including consistency in providing balanced nutrition and fathers’ involvement in stunting prevention practices. Conclusion: athers’ and mothers’ attitudes play an important role in stunting prevention efforts. Strengthening health education programs that actively involve both parents is essential to improve awareness and consistency in stunting prevention behaviors within the family.